Pernikahan Daring Pada Masa Pandemi Covid-19 Dalam Pandangan Hukum Islam - Tanuri (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2022)
The corona virus epidemic, which will begin in 2020 and restrict a variety of human activities, is what spurred this research. The government's goal of prohibiting large crowds and gatherings of individuals in one area has led to several secondary issues, including marital affairs, which by their very nature must nonetheless take place. Going online is a viable choice if you want to be married without breaking any laws. Through this paper, we want to reveal how online marriage is during the COVID-19 pandemic in terms of Islamic law. The method used in this research is normative law by examining the rules of Islamic law, positive law, and comparing them with existing problems. The results of this study indicate that the online marriage contract is in accordance with current Islamic law. So, in the view of Islamic law, distance separation is not the main problem, but the important thing from the same goals and thoughts in marriage.